The winter fortress : the epic mission to sabotage Hitler's atomic bomb - Bascomb, Neal (Houghton Mifflin Harcourt, 2016)
"Documents the Allied raid against occupied Norway's Vermork hydroelectric plant, the world's only supplier of an essential ingredient needed by the Nazis to build an atomic bomb, citing the teamwork of British Special Ops, a brilliant scientists and refugee Norwegian commandos that foiled Hitler's nuclear ambitions,"--NoveList.